Green Employee Engagement for Environmental Sustainability and Operational Excellence in the Palm Oil Industry: A Systematic Literature Review - Posma Sinurat; Pawenary Pawenary; Safuan Safuan; Edi Hamdi (Politeknik Siber Cerdika Internasional, 2026)
Background: Palm oil industry supports growth but faces environmental scrutiny; green employee engagement’s role in sustainability and operational excellence remains underexplored. Objective: To develop a conceptualization of green employee engagement and to examine the contribution of green employee engagement to environmental sustainability and to the operational performance of palm oil mills, through a Systematic Literature Review (SLR). Methods: PRISMA review of 19 articles (2019–2025), retrieved through Scopus, Web of Science, ScienceDirect, Emerald, MDPI, and Google Scholar. Inclusion criteria included peer-reviewed articles published only in English or Bahasa Indonesia; articles published in Q1–Q4 or SINTA 1–3 journals focused specifically on Green HRM (or its constructs) and environmental/operational performance. Results: Employees are now at the center of the green agenda, and this has become one of the strategic drivers of organizational transformation. HR drives systemic change through Green HRM, a powerful mediating system, by investing in operational innovation, strong green culture, efficient green training, sustainable talent development, and green recruitment. This directly assists HR managers and policymakers when designing work systems that improve energy efficiency, reduce waste, and increase compliance. Conclusion: Green employee engagement is a tool in this regard, more than a management practice; it goes straight to the core of shifting the industry. This synthesis reveals three prominent patterns: (1) GHRM integration facilitates green culture, (2) the role of HR as a strategic enabler in systemic implementation, and (3) green employee engagement as a driver of operational efficiency and competitiveness in the palm oil industry.